Effect of viscoelasticity on skin pain sensation - Fusheng Liu; Chenghai Li; Shaobao Liu; Guy M. Genin; Guoyou Huang; TianJian Lu; Feng Xu (Theoretical and Applied Mechanics Letters, 2015)
Pain sensation may appear under long-lasting mechanical stimulation. Although people have the experience that pain sensation generally decreases with time while the stimulation remains, the underlying mechanism remains elusive. We experimentally studied the thermal and strain rate-dependent viscoelastic behavior of skin in uniaxial stretch and numerically investigated the effects of temperature and strain rate on pain sensation. The results indicate that the viscosity of skin tissue decreases with increasing temperature and reducing strain rate, which subsequently decreases the discharge frequency of skin nociceptor and thus relieves the pain sensation. The results would contribute to the understanding of pain relief mechanism and optimizing for mechanical treatment.